Epidemiology of coronary heart disease and acute coronary syndrome - Sanchis-Gomar, Fabian (Ann Transl Med, 2016)
The aim of this review is to summarize the incidence, prevalence, trend in mortality, and general prognosis of coronary heart disease (CHD) and a related condition, acute coronary syndrome (ACS). Although CHD mortality has gradually declined over the last decades in western countries, this condition still causes about one-third of all deaths in people older than 35 years. This evidence, along with the fact that mortality from CHD is expected to continue increasing in developing countries, illustrates the need for implementing effective primary prevention approaches worldwide and identifying risk groups and areas for possible improvement.